If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -8 + -7x + 2 = 0 Reorder the terms: -8 + 2 + -2x + -7x = 0 Combine like terms: -8 + 2 = -6 -6 + -2x + -7x = 0 Combine like terms: -2x + -7x = -9x -6 + -9x = 0 Solving -6 + -9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -9x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -9x = 0 + 6 -9x = 0 + 6 Combine like terms: 0 + 6 = 6 -9x = 6 Divide each side by '-9'. x = -0.6666666667 Simplifying x = -0.6666666667
| -3x+2y=-33 | | (x*x)+18x+5=0 | | 225-6x=30x+17 | | h=-16t^2+80t+6 | | f(x)=-0.5x^3+2.5x^2+2x-10 | | 6.4x-3.5x=-46.4 | | -5g-7=3 | | -2n-15=61 | | f(x)=x^2+5x-2(2f(2)) | | f(x)=x^2+5x-2 | | 6+10x=42 | | [2-5(6+11)]= | | -4x+9y=-27 | | -3v+32=-7v+2(1-3v) | | 5x+6y=-18 | | -7x-2y=52 | | 2x^2-2304=0 | | 3+10=80-4 | | 4x+6y=-26 | | (8x+2)-4=18 | | 331x+6=7 | | 13+5= | | 18q=-11 | | q+13=61 | | -5x+49=-8(x-8) | | 8x-110=2x-14 | | 3+2x=x-5 | | 11z^2=-18 | | s+9=37 | | 2+3m= | | b^2-4b-b+4= | | w-8=-2 |